The Influence of Culture on Client-Counselor Relationships in Cultural Diversity Adaptation Counseling - Deliati; Firman; Yarmis Sukur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aims to analyze the influence of culture in the relationship between clients and counselors in the context of adaptation counseling. Using a qualitative approach, this study explores how cultural differences affect the counseling process and client adaptation in cultural diversity. The method used in this study is a literature review method. The results of the study indicate that understanding and recognizing cultural differences in counselor-client relationships can increase the effectiveness of counseling. This article also discusses practical implications for counseling practitioners in promoting more inclusive and culturally sensitive practices.